PABRIK KIMIA METIL ETIL KETON DARI 2-BUTANOL KAPASITAS 60.000 TON/TAHUN - , AULIA MAHANI NASIR, Ir. Suprihastuti Sri Rahayu, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia have many industries that still import their raw material from overseas. Metil etil keton is one of the compounds that is imported by industries in Indonesia, so that the industry of metil etil keton has a good prospect to be depeloped in Indonesia. In addition to fulfill the domestic needs, this industry also being prepared to compete in the international free market. This plant produces methyl ethyl keton by dehidrogenating secondary butanol in a multitube reactor. Beside mehyl ethyl keton, this plant also produce hydrogen that should be separated from the other compounds by using partial condensor. To get 99% purity of methyl ethyl keton, the mixture from separator is distilled to separate the methyl ethyl keton from the remaining secondary butanol and the water as impurity. This plant is designed for annual capacity of 60,000 ton of methyl ethyl ketone as the main product, 1,671.89 ton of hydrogen 80,4% (19,34% MEK, 0,24% 2-Butanol, 0,02% H2O) as the side product, and the need of secondary butanol raw material in amount of 62,088 ton, and zinc oxide as catalyst in amount of 4.7 ton. This plant operates continuously for 330 days The water needed to run this plant is 82.545 m3/hour, and 1.281 m3/hour of fuel oil. Every hour, this plant needs 514.29 kW of electricity and 2,067.45 m3/hour of air (1 atm, 30 oC). The steam (9,1 atm, 350 oF) needed in this plant is 13,642 kg/hour. On the land of 30,000 m2, this plant is planned to be built in Cilegon, West Java province. The employers needed to run this plant is predicted as more as 114 persons. From the economic analysis it is obtained that, this plant requires a fixed capital investment of $ 8,305,284.976 and Rp 65,031,074,295 and working capital as much as $ 441,272.9689 and Rp 283,934,262,010. A feasibility study concludes an ROI before taxes of 46,65 %, and ROI after taxes 27,99 %. POT before taxes is 1.77 years and POT after taxes is 2.63 years. DCFRR is 18.41%, BEP is 48%, and SDP is 33,81%. Based on this feasibility study, can be concluded that this methyl ethyl ketone from secondary butanol plant is economically feasible.